The peripheral blood standard values in newborns in Dr. Pirngadi Hospital Medan - Djaman Purba; Nasril Nazir; M. Djalinson Purba; Rehmamana Sembiring; Noersida Raid; S. M. Manoeroeng; Helena Siregar (Paediatrica Indonesiana, 1982)
A study of peripheral blood standard values was carried out on 100 healthy full term newborns, with normal deliveries to healthy mothers in Dr. Pirngadi Hospital Medan, comprising of 60 males and 40 females.The newborns were divided into three groups according to their birth weight.There were no significant differences of the average value of peripheral blood counts between group I, II and III neither between males and females.The average value of hemoglobin concentration with Sahli is lower than that with Cyan method, which is significantly different (p<0.00I).The average values found in this study on newborn babies of 24 hours of age with term deliveries were as follows:Hemoglobin Sahli                             :               16.13 gm %Hemoglobin Cyan                            :               17.88 gm %Leucocyles                                      :               16,512/cu mmHematocrit                                      :               56.4 %Reticulocytes                                   :               40.06 %Erythrocyte sedimentation rate           :               3.09/1st hour